Pregnancy Married in The Perspective of Four Madzhab and Compilation of Islamic Law (KHI) - Ahmad Mustarsidin; Akhmad Khisni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Ulama were differed concerning in pregnancy married. Pregnancy married is a marriage that takes place between men with a woman who is pregnant because of adultery. The opinion of the problem in this paper on the pregnancy married in the perspective of four madzhab and compilation of islamic law is not the same. Madzhab Hanafi and Syafi’i absolutely allow pregnancy married, but in terms of intercourse they have different opinions. Hanafi view when marrying is that impregnates the intercourse is allowed after the marriage ceremony without waiting for the wife gave birth to first, but if that is not who got married, the husband should not intercourse his wife to give birth first. Syafi’i found men who married the pregnant woman is absolutely allowed to have intercourse, both the man who impregnated or not. Instead, Maliki and Hanbali implicitly prohibits pregnancy married, had to wait for the woman giving birth. Even in the Hanbali sect imposed additional conditions, the woman should repent significantly to Allah SWT. Both schools of thought have asserted that the law is invalid pregnancy married. The Compilation of Islamic Law has its own opinion. The provisions on pregnancy married in the Compilation of Islamic law under Article 53 which consists of three (3) paragraph.Keywords: Pregnancy Married, Compilation of Islamic Law.